صورة المرأة فى روايات عبد الحميد جودة السحار : دراسة تحليلية نقدية /‏ - Maimanah Samsuri
This literary study looks into and analyses picture of women in the novels written by ῾Abd al-Hamid Jawdah al-Sahar. The aim is to demonstrate their picture and characters. The study also examines the congruence of Islamic principles and values to these pictures. Basically, the study focuses on three novels namely: “al-Niqab al-Azraq”, “Amu al-῾Arusah”, and “al-Mustanq῾a”. The analysis derived from each of these novels is based on the summaries of related stories, plots, characters and pictures of the women in the novels. The methodology undertaken by the study covers two approaches. Through the library research by collecting data were collected from books, journals and the Internet, followed by critical data analysis that produced comments and critics. The elements that constituted the novels which presented the women's picture were extracted and then critically and literarily analyzed. The study concludes that ῾Abd al- al-Hamid Jawdah al-Sahar eloquently presented the women's picture about through their reputations and rights in their society. In addition, by comparing their negative and positive pictures, he left the readers to choose the better one.